2022
DOI: 10.1186/s42269-022-00697-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between preference and e-learning readiness among the Bangladeshi female nursing students in the COVID-19 pandemic: a cross-sectional study

Abstract: Background The COVID-19 pandemic jeopardized the traditional academic learning calendars due to the closing of all educational institutions across the globe. To keep up with the flow of learning, most of the educational institutions shifted toward e-learning. However, the students’ e-learning preference and e-learning readiness did not identify, particularly among the Bangladeshi female nursing students, where those can pose serious challenges. A cross-sectional study was carried out among the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
(45 reference statements)
3
15
0
Order By: Relevance
“…The age of student nurses has found a significant difference in self-efficacy with online learning, which means that as they age, they understand the usefulness of online education, especially in this pandemic. This result is consistent with Kabir et al (2022) finding that age has been significantly associated with the use of technology. Therefore, when creating online sessions, nursing education teachers should improve their online course development and examine the key parameters such as age.…”
Section: Discussionsupporting
confidence: 92%
“…The age of student nurses has found a significant difference in self-efficacy with online learning, which means that as they age, they understand the usefulness of online education, especially in this pandemic. This result is consistent with Kabir et al (2022) finding that age has been significantly associated with the use of technology. Therefore, when creating online sessions, nursing education teachers should improve their online course development and examine the key parameters such as age.…”
Section: Discussionsupporting
confidence: 92%
“…This also negatively affected the development of students' psychomotor skills in a clinical setting. In the literature, it was stated that online education is not effective in acquiring clinical and technical skills (Abbasi et al, 2020;Luyben et al, 2020;Kuliukas et al, 2021;), and it was also noted that online education negatively affects students' self-confidence and their preparation for the profession (Choi et al, 2020;Topuz et al,2021;Kabir et al, 2022). The results of the study showed that, similar to our study, online education is not sufficient to develop clinical skills, professionalism and self-confidence.…”
Section: Discussionsupporting
confidence: 62%
“…The possible reason could be as they were more likely to expose to distance learning and technology based service usability. [42][43][44][45] A similar study measuring nursing students' readiness to use telenursing was carried out in Poland. 46 Amazingly, 69.49% of the students reported that they would be very likely to include telenursing in their course curriculum.…”
Section: Discussionmentioning
confidence: 99%